Gold(I)-catalyzed formation of benzo(b)furans from 3-silyloxy-1,5-enynes - Hashmi, A. Stephen K.; Yang, Weibo; Rominger, Frank (Angewandte Chemie. International edition, 2011)
Sport of kings: A new gold(I)-catalyzed transformation has been developed that occurs under mild conditions and proceeds by an expected substituent “castling” (see red and blue circles in scheme) to give efficient access to benzo[b]furans from the easy to obtain 3-silyloxy-1,5-enynes (IPr=N,N′-bis(2,6-diisopropylphenyl)imidazol-2-ylidene, NTf2=bis(trifluoromethylsulfonylimide).
Gesehen am 31.08.2022